The Greek public debt problem - Michalis Nikiforos; Dimitri B. Papadimitriou; Gennaro Zezza (Levy Economics Institute of Bard College, 2016)
This paper examines the issue of the Greek public debt from different perspectives. We provide a historical discussion of the accumulation of Greece's public debt since the 1960s and the role of public debt in the recent crisis. We show that the austerity imposed since 2010 has been unsuccessful in stabilizing the debt while at the same time taking a heavy toll on the Greek economy and society. The experience of the last six years shows that the country's public debt is clearly unsustainable, and therefore a bold restructuring is needed. An insistence on the current policies is not justifiable either on pragmatic or on moral or any other grounds. The experience of Germany in the early post-World War II period provides some useful hints for the way forward. A solution to the Greek public debt problem is a necessary but not sufficient condition for the solution of the Greek and wider European crisis. A broader agenda that deals with the malaises of the Greek economy and the structural imbalances of the eurozone is of vital importance.
Keywords: E62; F34; F41; N10; N94; 330; Greece; Public Debt; Austerity; Eurozone; Crisis